2015
DOI: 10.1111/ejn.13093
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transformations between superior colliculus visual and motor response fields during head‐unrestrained gaze shifts

Abstract: We previously reported that visuomotor activity in the superior colliculus (SC)--a key midbrain structure for the generation of rapid eye movements--preferentially encodes target position relative to the eye (Te) during low-latency head-unrestrained gaze shifts (DeSouza et al., 2011). Here, we trained two monkeys to perform head-unrestrained gaze shifts after a variable post-stimulus delay (400-700 ms), to test whether temporally separated SC visual and motor responses show different spatial codes. Target posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
86
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(98 citation statements)
references
References 117 publications
(206 reference statements)
11
86
1
Order By: Relevance
“…However, it has been suggested that saccade-related hemispheric asymmetry in PPC could be influenced by factors such as latency and dynamics (Yang and Kapoula, 2004; Vergilino-Perez et al, 2012). One thing conspicuously missing in both our Delay and Response data was contralateral selectivity in the superior colliculus (Wurtz and Albano, 1980; Munoz, 2002; Gandhi and Katnani, 2011; Sadeh et al, 2015), but this is likely related to the limitations of standard fMRI techniques in revealing subcortical activation.…”
Section: Discussionmentioning
confidence: 92%
“…However, it has been suggested that saccade-related hemispheric asymmetry in PPC could be influenced by factors such as latency and dynamics (Yang and Kapoula, 2004; Vergilino-Perez et al, 2012). One thing conspicuously missing in both our Delay and Response data was contralateral selectivity in the superior colliculus (Wurtz and Albano, 1980; Munoz, 2002; Gandhi and Katnani, 2011; Sadeh et al, 2015), but this is likely related to the limitations of standard fMRI techniques in revealing subcortical activation.…”
Section: Discussionmentioning
confidence: 92%
“…However, they could not fully explain the observed pattern of results, as we did characterize strong eye-centered and head-centered representations in all regions and modalities, indicating that multiple reference frames were active, beyond hybrid signals. Indeed, there is consensus in the literature that eye movements or changes in eye position affect visual and auditory signals in all of the areas we tested here (Van Opstal et al, 1995;Klier et al, 2001;DeSouza et al, 2011;Lee and Groh, 2012;Sadeh et al, 2015), Sparks, 1984, 1987b, a), (Cassanello and Ferrera, 2007) (Sommer and Wurtz, 2006;. (Keith et al, 2009;Sajad et al, 2015;Sajad et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the enhancement of the visual response may reflect internal changes, e.g., greater visual attention and/or increased target salience. Although the interpretation of a flexible visual-movement continuum is based on a wealth of studies that have found little differences between visual and saccade-related responses of visuomovement neurons, it is important to mention recent studies that have shown that a systematic transformation occurs between the visual and motor responses, from representing target location in space to representing actual movement metrics (Sadeh et al, 2015;Sajad et al, 2015). Our results suggest a lack of strong functional distinction between the visual and movement bursts, but specifically with respect to initiating the movea b Figure 7.…”
Section: Discussionmentioning
confidence: 99%